Determinants of household savings among family hope program beneficiary families - Rian Dwi Utami; Gunawan, Ratna Setyawati; Gunawan, Diah Setyorini (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2025)
This research examines the effect of income, age of the household head, number of children, and education level of the household head on household savings. Data was collected through direct interviews with respondents from a total population of 160 households, with a sample size of 62 households determined using the Taro Yamane formula and proportional random sampling. The collected data was analyzed using multiple linear regression. The findings reveal that partially, income has a positive effect on household savings, while the number of children has a negative effect on household savings. The age of the household head and education level of the household head have no significant effect on household savings. Furthermore, income, age of the household head, number of children, and education level of the household head simultaneously have a significant effect on household savings. The first of the research's implications is the necessity of empowering housewives by making use of the village's ability to raise household income. Second, in order to prevent children from becoming a burden in the future, the government, through the National Population and Family Planning Agency runs campaigns about the number of children and the spacing between pregnancies.